The Educational Function of Museums in the Vicinity of Montreal: With Special Reference to Historical Museums and Sites - Ferrabee, Henry Gilbert (Université McGill, 1953)
Keywords: Musées; Université McGill

Ancient Greek Gold and Silver Coins in the McGill University Collection - Shlosser, Franziska E. (Université McGill, 1971)
Keywords: Grecs; Numismatie; Université McGill

La physique à McGill entre 1920 et 1940: la réception de la mécanique quantique par une communauté scientifique périphérique - Gingras, Yves (HSTC Bulletin, 1981)
Keywords: Physique; Université McGill

Science and Engineering at McGill and Queen's Universities and the University of Toronto, 1880s to 1920s - Creet, Mario (Université Queen's, 1993)
Keywords: Ingénieurs; Université McGill

La physique à McGill entre 1920 et 1940: la réception de la mécanique quantique par une communauté scientifique périphérique - Gingras, Yves (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 1991)
Keywords: Physique; Université McGill

A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Chimie; Université McGill

Medical Genetics at McGill: The History of a Pioneering Research Group - Canning, Christopher; Weisz, George; Tone, Andrea; Cambrosio, Alberto (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2013)
Keywords: Médecine; Université McGill

"An Ocean of Noise": H.E. Reilley and the Making of a Legitimate Social Problem, 1911-45 - Rudy, Jarrett; Kenny, Nicolas; Fahrni, Magda (Journal of Canadian Studies / Revue d'études canadiennes, 2017)
Keywords: Physique; Université McGill

L’Office provincial des recherches scientifiques et le développement de la science au Québec, 1937-1960 - Almeida, Mike (Revue d'histoire de l'Amérique française, 2002)
Keywords: Université McGill; Université de Montréal

Émergence et évolution de la recherche en mathématiques au Québec, 1945-1984 - Foisy, Martine; Gingras, Yves (Société mathématique du Canada, 1945-1995. Vol. 1: Les mathématiques au Canada, 1995)
Keywords: Université McGill; Université de Montréal

L'institutionnalisation de la recherche en milieu universitaire et ses effets - Gingras, Yves (Sociologie et sociétés, 1991)
Keywords: Université McGill; Université de Montréal

John William Dawson: Faith, Hope, and Science - Sheets-Pyenson, Susan (McGill-Queen's University Press, 1996)
Keywords: Dawson, William; Université McGill

De Freud au Père Mailloux : transmission, paradoxes et institutionnalisation : une histoire des origines de la psychanalyse au Québec - Adam-Vézina, Élodie (Université du Québec à Montréal, 2017)
Keywords: Psychologie; Université McGill; Université de Montréal

Designing the Medical Museum - Adams, Annmarie (Healing Spaces, Modern Architecture, and the Body, 2018)
Keywords: Musées; Médecine; Université McGill

Des frontières culturelles en santé mentale au Canada? Entre psychiatrie, démographie et sociologie, retour sur les études de H.B.M. Murphy en épidémiologie - Delille, Emmanuel (Revue d'histoire de l'Amérique française, 2021)
Keywords: Médecine; Sociologie; Université McGill

Carrie Derrick (1862-1941) and the Chair of Botany at McGill - Gillett, Margaret (Despite the Odds: Essays on Canadian Women and Science, 1990)
Keywords: Botanique; Derrick, Carrie; Université McGill

The Design of the Peter Redpath Museum at McGill University: the Genesis, Expression and Evolution of an Idea about Natural History - Bronson, Susan D. (Université de Montréal, 1992)
Keywords: Musées; Redpath (musée); Université McGill

Osler's Autopsies: their Nature and Utilization - Rodin, Alvin E. (Medical History, 1973)
Keywords: Médecine; Osler, William; Université McGill

Engineering Education and Research in Montreal: Social Constraints and Opportunities - Gingras, Yves; Gagnon, Robert (Minerva, 1988)
Keywords: Ingénieurs; Université McGill; École polytechnique

The Design of the Peter Redpath Museum at McGill University: The Genesis, Expression, and Evolution of an Idea About Natural History - Bronson, Susan (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1992)
Keywords: Musées; Redpath (musée); Université McGill

Stones and Bones and Skeletons: the Origins and Developments of the Peter Redpath Museum, 1882-1912 - Sheets-Pyenson, Susan (McGill Journal of Education, 1982)
Keywords: Musées; Redpath (musée); Université McGill

Nobel pursuit. How Ernest Rutherford's Montreal research won the world's top science prize - Hardy, John (Canada's history, 2023)
Keywords: Brooks, Harriet; Physique; Université McGill

Histoire de la médecine au Québec, 1800-2000. De l'art de soigner à l'art de guérir - Goulet, Denis; Gagnon, Robert (Septentrion, 2014)
Keywords: Hôpitaux; Médecine; Université McGill; Université de Montréal

John Stuart Foster, McGill University and the Renascence of Nuclear Physics in Montreal, 1935-1950 - Thomas, Jerry (Historical Studies in the Physical Sciences, 1984)
Keywords: Foster, John Stuart; Physique; Université McGill

Anatomically Incorrect: Bodysnatching in the Nineteenth Century - Rankin, Matthew (The Beaver, 2002)
Keywords: Criminalité; Médecine; Université McGill; Étudiants

It Was a Man's World: Blaine Baker and the Writing of Canadian Legal History, 1981-2018 - Young, Brian (Law, Life, and the Teaching of Legal History. Essays in Honour of G. Blaine Bake, 2022)
Keywords: Ensiegnants; Histoire; Historiens; Université McGill

La réception des rayons X au Québec: radiographie des pratiques scientifiques au Québec - Gingras, Yves (Sciences et médecine au Québec. Perspectives socio-historiques, 1987)
Keywords: Médecine; Physique; Technologie médicale; Université McGill

La réception des rayons X au Québec: radiographie des pratiques scientifiques - Gingras, Yves (A New Kind of Ray: the Radiological Sciences in Canada - les Sciences radiologiques au Canada, 1895-1995, 1995)
Keywords: Médecine; Physique; Technologie médicale; Université McGill

The Science of Social Redemption. McGill, the Chicago School, and the Origins of Social Research in Canada - Shore, Marlene (University of Toronto Press, 1987)
Keywords: Dawson, Carl; Marsh, Leonard; Sociologie; Université McGill

Les hommes-relais de la bactériologie en territoire québécois et l’introduction de nouvelles pratiques diagnostiques et thérapeutiques (1890-1920) - Goulet, Denis; Keel, Othmar (Revue d'histoire de l'Amérique française, 1993)
Keywords: Hôpital Notre-Dame; Médecine; Université McGill; Université de Laval à Montréal; Université de Montréal

Getting a Job Done and Doing It Well: Dr. Blossom Wigdor, Psychologist and Gerontologist - Beaveridge, Janice (Despite The Odds: Essays on Canadian Women and Science, 1990)
Keywords: Femmes; Gérontologie; Psychologie; Université McGill; Wigdor, Blossom

Duncan McEachran 1841-1924 / Duncan McEachran 1841-1924 - Fulleringer, Pat (Héritage Dorval, 2003)
Keywords: McEachran, Duncan McNab; Université McGill; École de médecine vétérinaire

Encountering Maude Abbott - Adams, Annmarie (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2018)
Keywords: Abbott, Maude E.; Femmes; Histoire; Hôpitaux; Musées; Médecine; Royal Victoria Hospital; Université McGill

Prehistoric Montreal - Lighthall, W. D. (Université McGill, 1920)
Keywords: Archéologie; Autochtones; Dawson, William; Hochelaga; Lighthall, William Douw

Science et technologie à Montréal: la longue naissance d'une ville du savoir - Trépanier, Michel (Histoire de Montréal et de sa région, 2012)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin, Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

Science and Technology: The Coming of Age of a City of Knowledge - Trépanier, Michel (Montreal: The History of A North American City, 2018)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin, Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

Suspended Conversations: Private Photographic Albums in the Public Collection of the McCord Museum of Canadian History - Langford, Martha (Université McGill, 1997)
Keywords: Musée McCord; Musées; Photographie

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées

Du silence à l'affirmation: Women Making History in Point St. Charles - Kruzynski, Anna (Université McGill, 2004)
Keywords: Femmes; Pointe-Saint-Charles; Quartiers

The Petrology of a Part of Westmount Mountain near Summit Circle, Montreal - Malouf, Stanley Edward (Université McGill, 1936)
Keywords: Géographie physique

[Re]Claiming Montreal’s Memory: Demolition and the Photography of Edith Mather - Southcott, Tanya (Université McGill, 2013)
Keywords: Patrimoine; Paysages; Photographie; Rues

The Practice of Engineering Geology during Pre-Construction Investigations in the Montreal Area - Eivemark, Michael M. (Université McGill, 1971)
Keywords: Géologie; Ingénieurs

The Stories Told: Indigenous Art Collections, Museums, and National Identities - Dickenson, Rachelle (Université McGill, 2005)
Keywords: Autochtones; Musées

Black slavery, historians and textbooks: A study of the representation of enslaved people of African descent in Quebec's historiography and history textbooks - Roethlisberger, Susanne (Université McGill, 2020)
Keywords: Africains; Esclaves; Histoire